Osteogenesis Imperfecta Type III: Case Report and Comprehensive Analysis of Phenotypic Classification, Genetic Causes, and Therapeutic Approaches - Graça, Natã (2025)
Osteogenesis imperfecta (OI), known as brittle bone disease, is a genetic condition that affects the extracellular matrix of the skeletal system, causing bone fragility and potential impacts on other organs. Its prevalence varies from approximately 1 in 10 000 to 20 000 births and is associated with various genetic mutations. We report a case of a 14-month-old female patient diagnosed with OI type III, characterized by short stature, dental abnormalities, and bone fragility. Medical history includes effectively treating fevers, gastrointestinal, and respiratory issues. X-rays revealed fractures in bilateral femurs and humeri. She underwent femur surgery and continues to experience frequent fractures, unable to ambulate, under intensive medical care. OI is a genetic condition presenting with severe bone fragility, short stature, and progressive deformities, necessitating accurate diagnosis and effective treatment to improve quality of life.